Advanced Computing in Industrial Mathematics 12th Annual Meeting of the Bulgarian Section of SIAM December 20-22, 2017, Sofia, Bulgaria Revised Selected Papers - Georgiev, Krassimir; Todorov, Michail; Georgiev, Ivan.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book gathers the peer-reviewed proceedings of the 12th Annual Meeting of the Bulgarian Section of the Society for Industrial and Applied Mathematics, BGSIAM'17, held in Sofia, Bulgaria, in December 2017. The general theme of BGSIAM'17 was industrial and applied mathematics, with a particular focus on: high-performance computing, numerical methods and algorithms, analysis of partial differential equations and their applications, mathematical biology, control and uncertain systems, stochastic models, molecular dynamics, neural networks, genetic algorithms, metaheuristics for optimization problems, generalized nets, and Big Data. .
Method for indoor localization of mobile devices based on AoA and Kalman filtering -- Cross-Validated Sequentially Constructed Multiple Regression -- How to assess multi-population genetic algorithms performance using intuitionistic fuzzy logic -- Perturbation analysis of a nonlinear matrix equation arising in Tree-like stochastic processes -- On Two-Way Generalized Nets -- Variational methods for stable time discretization of first-order differential equations -- Numerical solutions of ordinary fractional differential equations with singularities -- Preliminary analysis of the dynamics of multifractal parameters of the Dow Jones Industrial Average -- Testing performance and scalability of the pure MPI model versus hybrid MPI-2/OpenMP model on the heterogeneous supercomputer Avitohol -- Analyses and Boolean operation of 2D polygons -- Ant Colony Optimization Algorithm for Workforce Planning: Inuence of the Algorithm Parameters -- Convergence of homotopy perturbation method for solving of two-dimensional fuzzy Volterra functional integral equations -- Iterative method for numerical solution of two-dimensional nonlinear Urysohn fuzzy integral equations.
Keywords: Computational intelligence; Artificial intelligence; Computer science -- Mathematics; Computational Intelligence; Artificial Intelligence; Mathematical Applications in Computer Science